Religious ethnocentrism as a potential birth of lone-wolf terrorism in Indonesia - Wahyu Agung Sukhamdani; Zora Arfina Sukabdi (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
acts of terrorism and radicalism that have taken place in Indonesia often lead fundamental questions about the Indonesian nation’s sense of nationalism. Moreover, the perpetrators of the action are Indonesian citizens, so it is interesting to study in more depth howithe Indonesianness of Indonesian citizens (WNI), so it is interesting to study more deeply how Indonesian citizens are when events occur that sahe Indonesia’s diversity. Indonesia, which is plural and multi-cultural, was shaken by incidents of radicalism and terrorism. This paper aims to provide an overview regarding the influence of religious ethnocentrism on the phenomenon of lone-wolf terrorism in Indonesia. This paper was prepared using a qualitative approach, namely a deks study or literature review. Some of the data used in qualitative research with the desk study model are literatur related to the research issues raised. Data sources can be in the form of research result, mass medianews, report and previous studies that have discussed the issues on cultural, Islamic and Indonesian discourses are used to reveal literature data related to the potential for terrorism. The result show that thae emergence of violence follows a predictable pattern, such as starting with hate speech directed at other groups and progessing to efforts to dehumanizw or promote the belief within their own group that other groups are”less humane”. At this time, views that look down on other groups become a wick that fuels agrressive behavior and leads to terrible deeds and situation. Seeing that one’s self is better than other parties also lead to give birth to act of terrorism that are carried out individually or known as lone wolves. The threat of terrorism with the lone wolf type has become a new trend in commiting acts of terror